Pemberdayaan Ibu-Ibu Pengurus RT 003/02 BSD Melalui Pelatihan Literasi Informasi, Manajemen UMKM Sederhana, dan Keterampilan Komunikasi Kolaboratif di Era Digital - Riastri Novianita; Bobby Octavia Yuskar; Ondy; Cindya Yunita Pratiwi (CV Edujavare Publishing, 2026)
This community service program aims to improve the capacity of women administrators of RT 003/002 BSD through training in information literacy, simple MSME management, and collaborative communication skills in the digital era. This activity was motivated by the need to strengthen the role of community organizations in adapting to digital transformation, particularly in accessing information, managing small businesses, and improving organizational communication. Preliminary observations indicated that participants had limited knowledge in digital information management, simple financial administration, and effective communication practices. The implementation method consisted of training sessions, interactive discussions, practical exercises, and mentoring activities. The program involved 15–20 participants and was conducted through several stages, including preliminary observation, preparation of training materials, program implementation, and evaluation. The training focused on improving participants’ understanding of digital information literacy, basic financial recording for small businesses, simple digital marketing strategies, and effective communication within community organizations. The results showed an improvement in participants’ knowledge and practical skills in utilizing digital media, managing small business finances, and strengthening communication among community members. Participants also demonstrated increased awareness in using digital platforms productively. This program is expected to strengthen women's roles as agents of community empowerment and support sustainable social and economic development at the neighborhood level.